Biogenic synthesis, molecular docking, biomedical and environmental applications of multifunctional CuO nanoparticles mediated Phragmites australis - Kocabas, Buket Bulut; Attar, Azade; Yuka, Selcen Ari; Yapaoz, Melda Altikatoglu (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2023)
The demand for metal nanoparticles is increasing with the widening application areas while causing environ-mental impact including pollution, toxic byproduct generation and depletion of natural resources. Incorporating natural materials in nanoparticle synthesis can contribute toward environmental sustainability. This paper is concerned with the biogenic synthesis of copper oxide nanoparticles (CuONPs) mediated by the plant species Phragmites australis. UV-vis, FT-IR, TEM and SEM studies were used to characterize the obtained CuONPs. The synthesized nanoparticles' antibacterial efficacy against Escherichia coli and Staphylococcus aureus was assessed. The CuONPs' reducing power, total phenolic component content, and flavonoid content were all calculated. Additionally, the dye removal abilities of copper oxide nanoparticles using Brilliant Blue R-250 were studied. The CuONP synthesis was assessed morphological by change of color and in the UV-vis analysis by the SPR band around 320 and 360 nm. FT-IR was used to monitor the functional groups present in the synthesized CuONPs. The obtained CuONPs were spherical and between 70 and 142 nm in size, according to the SEM data and TEM analyses were in accordance with SEM results. Using disk diffusion, the CuONPs demonstrated substantial antibacterial efficacy against S. aureus and E. coli, with inhibition zones of 18.5 +/- 0.8 and 12.7 +/- 0.6 mm, respectively. The MBC and MIC values were 62.5 mu g/mL against S. aureus and 125 mu g/mL against E. coli. The antioxidant abilities of P. australis and CuONPs were also confirmed. The CuONP solution's total phenolic substance content was 9.44 mu g of pyrocathecol equivalent per milligram of nanoparticle, and its total flavonoid content was 16.24 mu g of catechin equivalent per milligram of nanoparticle. Additionally, the synthesized CuONPs were found to be well effective on industrial dye removal by demonstrating high decolorization of 98 %. Also, the antibacterial activity of CuONPs was investigated through the interactions with S. aureus FtsZ, dihydropteroate synthase and thymidylate kinase. In silico molecular docking analysis was applied in the confirmation of the binding sites and interactions of active sites. CuONP showed-9.067,-8,048, and-7.349 kcal/mol of binding energies in molecular docking analysis of FtsZ, dihydropteroate synthase and thymidylate kinase proteins respectively. The results of this study suggested the antimicrobial, antioxidant and decolorative effect of syn-thesized CuONPs that can be apply in multiple areas of R & D and industry.
Keywords: Antimicrobial activity; Biogenic synthesis; Copper oxide nanoparticles; Brilliant Blue R-250; Molecular docking; Phragmites australis; COPPER-OXIDE NANOPARTICLES; EXTRACT; BIOSYNTHESIS; ANTIOXIDANT; Biochemistry & Molecular Biology; Chemistry